How to Form Good Habits? A Longitudinal Field Study on the Role of Self-Control in Habit Formation - van der Weiden, Anouk; Benjamins, Jeroen; Gillebaart, Marleen; Ybema, Jan Fekke; de Ridder, Denise (Frontiers in Psychology, 2020)
When striving for long-term goals (e.g., healthy eating, saving money, reducing energy consumption, or maintaining interpersonal relationships), people often get in conflict with their short-term goals (e.g., tempting snacks, must-haves, getting warm, or being preoccupied with one’s own interests). Previous research suggests that people who are successful in controlling their behavior in line with their long-term goals rely on effortless strategies, such as good habits. In the present study, we aimed to track how self-control capacity affects the development of good habits in real life over a period of 90 days. Results indicated that habit formation increased substantially over the course of three months, especially for participants who consistently performed the desired behaviour during this time. Contrary to our expectations, however, self-control capacity did not seem to affect the habit formation process. Directions for future research on self-control and other potential moderators in the formation of good habits are discussed.